Blood and bone marrow findings in two pups with mucopolysaccharidosis type VII. (14th March 2021) - Corda, Erica; Swenson, Cheryl L.; Scott, Michael A.; Sledge, Dodd G.; Fyfe, John C.
Abstract: Routine blood smear findings in two of four 11‐day‐old mixed‐breed dog littermates were suggestive of a lysosomal storage disease (LSD) that was documented to be mucopolysaccharidosis type VII (MPS VII) by molecular testing. In this condition, a functional β‐glucuronidase deficiency results in the accumulation of glycosaminoglycans (GAGs) in cells and tissues where β‐glucuronidase is important in GAG degradation. Most neutrophils and a moderate number of lymphocytes within the blood had atypical cytoplasmic magenta inclusions. The bone marrow assessment from one of the two affected pups at 24 days of age revealed similar magenta granulation in myeloid precursor cells that was most prominent in promyelocytes and myelocytes. Moreover, atypical magenta material was present within vacuoles as well as extracellularly in some osteoblasts and macrophages. Histologic bone marrow sections revealed prominent vacuolation of osteoblasts, and some osteoclasts appeared separated from the bone by layers of osteoblasts or hematopoietic cells. At 2 months of age, the second affected dog showed moderate growth retardation and had similar but more prominent hematologic findings that extended to monocytes, eosinophils, and eosinophil precursors. It had an increased number of bone marrow macrophages with many vacuoles that could be seen cytologically to contain magenta material, and there was mild nonselective phagocytosis of hemic cells. Of the hematologic cells, inclusions were most prominent in promyelocytes, myelocytes, and macrophages, cells with relatively high β‐glucuronidase activity, and GAG exposure within lysosomes or lysosome‐like primary granules of granulocyte precursors.